Answer:
-3
Step-by-step explanation:
3+x=0
subtract 3 from 3, 0
subtract 3 from 0, -3
Answer:
1 4/35
Step-by-step explanation:
All I did was do 5/7 + 2/5.
Answer:
Combine like terms
Step-by-step explanation:
The first step in such equations is to simplify the equation which is done most often by combining like terms, and by combining like terms i mean for example:
1 + 5 + 3x = 4y + z
You will combine the like terms (those that can be added or subtracted):
6 + 3x = 4y + z
In our example, combining terms would be adding 2x/3 and 1x/3 to give
3x/3 + 2 = 5
The equation is now simple and easy to solve as you simplify 3x/3 to 1x and then proceed to rearrange the equation to yield the value of x
Hope this helps!
Answer:
omg someone help asap!1
Step-by-step explanation:
The area of a kite:
A = d1 * d2 / 2
d1 = BD = 8 units
48 = 8 * AC / 2
48 * 2 = 8 AC
96 = 8 AC
AC = 96 : 8 = 12
Answer: D ) 12 units